Evaluation of multi-layered graphene nano-platelet composite coatings for corrosion control part II – Cathodic delamination kinetics. (15th May 2018) - Glover, C.F.; Richards, C.A.J.; Williams, G.; McMurray, H.N.
Highlights: Graphene nano-platelets (GNP) reduce corrosion-driven cathodic delamination rates. GNP act principally to slow through-coating oxygen diffusion when coated on iron. When the GNP are coated on zinc, a galvanic couple is formed. The galvanic coupling of the GNP and zinc may displace cathodic oxygen reduction. Abstract: In-situ Scanning Kelvin probe (SKP) measurements are used to follow the corrosion-driven cathodic delamination kinetics of model coatings comprising graphene nano-platelets (GNP) dispersed in polyvinylbutyral (PVB) adherent to iron and zinc (galvanised steel). To reduce delamination rates by >90% (relative to unpigmented PVB) a GNP volume fraction of 0.056 is required on iron but only 0.028 on zinc. On this basis, together with work function and O2 permeability data it is proposed that the GNP acts principally to slow through-coating oxygen transport on iron; whereas on zinc a galvanic couple forms between zinc and GNP, displacing cathodic oxygen reduction.